Aplicação de β-glucanase em malte produzido a partir das cultivares de cevada BRS Cauê e Elis - Brazil, Crislane (2015)
The β-glucan content interferes directly in the malt quality parameters for the production of beer, especially in the filtration step. High β-glucans concentrations in barley require more time and temperature in the steeping and germination. The application of a commercial β-glucanase is an alternative to reduce the content of β- glucans. This study aimed to analyze the effect of the addition of β-glucanase in malt produced from barley cultivars BRS - Cauê and Elis (season 2013/2014) with a reduced germination time. The cultivars were subjected to micromalteações 96 hours (conventional) and 64 hours (reduced time) germination. The analyzes of β-glucans and quality of barley, malt and wort were performed according to the analytical methodology EBC (European Brewery Convention). The BRS - Cauê and Elis, germinated after 96 hours respectively showed the levels of 90.7 and 64.3 mg / L of β-glucans. The process with 64 h of germination resulted in levels over the maximum limit recommended by the EBC (178 mg / L), with 320.0 and 370.7 mg / L for the malts of BRS-Cauê and Elis cultivars respectively. The application of 100 mg / kg of malt β-glucanase produced in 64 h germination lowered β-glucan content to 74.7 (BRS-Cauê) and 81.7 mg / L (BRS-Elis). There was a reduction in β-glucan content of 76.67% for BRS - Cauê and 77.96% for BRS - Elis. Since for malt cultivar BRS - Cauê application of 25 mg / kg of the enzyme and the BRS - Elis application of 50 mg / kg was sufficient to obtain malt content according to recommended. The reduction in viscosity values were also observed. The application of commercial β-glucanase reduced the β-glucan content in malt produced in a shorter germination allowing the optimization of time in the malting process.